Double standards: why is pulse oximetry standard care, whereas tissue oximetry is not?. Issue 5 (October 2020) - Zhao, Xu; Xiao, Huaping; Cai, Junying; Meng, Lingzhong
Abstract : Purpose of review: Why is pulse oximetry a standard monitor, whereas tissue oximeter is not? Is this a double-standard treatment? Recent findings: There appears to be a lack of enthusiasm for a continual investigation into whether the use of pulse oximetry leads to reduced morbidity and mortality in acute care although there is no robust evidence attesting to its outcome benefits. In contrast, research investigating the outcome effectiveness of tissue oximetry-guided care is consistently ongoing. A recent randomized controlled trial involving 800 patients who underwent laparoscopic hysterectomy found that, although muscular tissue oxygen saturation-guided care did not reduce the overall occurrence of postoperative nausea and vomiting for all patients, it did reduce the occurrence of these symptoms in patients who had a body mass index ≥25. It was also observed that muscular tissue oxygen saturation increases when blood pressure falls following the administration of nicardipine. These studies highlight the persistence of interest in understanding the value of tissue oximetry in patient care. Summary: Pulse oximetry and tissue oximetry are treated differently although neither monitor has robust evidence attesting to its outcome benefits. This difference may root in the difference in the physiology they monitor, the cost, the ease of use/interpretation/intervention and the relevance to patient safety and care quality. Pulse oxygen saturation represents a vital sign, whereas tissue oxygen saturation is likely a quality sign; however, further research endeavors are required to fully understand how to best use tissue oximetry.